2017
DOI: 10.1038/ncomms14458
|View full text |Cite
|
Sign up to set email alerts
|

On the post-glacial spread of human commensal Arabidopsis thaliana

Abstract: Recent work has shown that Arabidopsis thaliana contains genetic groups originating from different ice age refugia, with one particular group comprising over 95% of the current worldwide population. In Europe, relicts of other groups can be found in local populations along the Mediterranean Sea. Here we provide evidence that these ‘relicts' occupied post-glacial Eurasia first and were later replaced by the invading ‘non-relicts', which expanded through the east–west axis of Eurasia, leaving traces of admixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
190
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(216 citation statements)
references
References 46 publications
(100 reference statements)
22
190
4
Order By: Relevance
“…In grey, the hypothesised recent expansion following human agriculture c . 8 ka (1001 Genomes Consortium, ; Lee et al ., ), and the colonization of Morocco from the Iberian peninsula.…”
Section: The Classic Model Of the History Of A Thalianamentioning
confidence: 99%
“…In grey, the hypothesised recent expansion following human agriculture c . 8 ka (1001 Genomes Consortium, ; Lee et al ., ), and the colonization of Morocco from the Iberian peninsula.…”
Section: The Classic Model Of the History Of A Thalianamentioning
confidence: 99%
“…The exceptional resources available in this species, including seed stocks collected from throughout Eurasia for over 75 y, have been a valuable tool for learning about the natural history of A. thaliana on this continent (1,2). Previous studies have shown that current variation in Eurasia is mainly a result of expansions and mixing from refugia in Iberia, Central Asia, and Italy/Balkans after the end of the last glacial period ∼10 kya (3)(4)(5)(6)(7)(8). The main finding of the recent analysis of 1,135 sequenced genomes was that a few Eurasian samples represent divergent relict lineages, whereas the vast majority derived from the recent expansion of a single clade (4).…”
mentioning
confidence: 99%
“…However, for some of these species, the survival of the Last Pleniglacial in southern European refugia has also been confirmed (Arrigo et al., ; Beck et al., ; Lee et al., ). Inferences have previously been made, based on the effects on genetic variation of both the south‐to‐north expansion after the glacial retreat and also on human‐induced, east‐to‐west dispersal in the Neolithic era (Arrigo et al., ; Lee et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…This region is especially important in respect of plant domestication and crop evolution (Zeder, ). Human‐induced changes of local landscapes due to the rise of agriculture, have introduced novel habitats which represent new opportunities for evolution and dispersal, not only for domesticated species but also for their commensals (Lee et al., and citations therein). Thus western Asia was found to be the evolutionary centre for many ruderal or weedy plant species (Arrigo et al., ; Beck et al., ; Cornille et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation